On some locally soluble infinite dimensional linear groups - Dashkova, O.Yu. (Algebra and Discrete Mathematics, 2008)
The author investigates nonabelian locally soluble linear groups of infinite fundamental dimension and of infinite section p-rank all of whose proper nonabelian subgroups of infinite section p-rank are of finite fundamental dimension. The solubility of these groups is proved.